MEANING AND REPRESENTATION OF BEAUTIFUL WOMEN IN THE FILM INSATIABLE - Veren Viriya; Daniel Susilo (Jurnal Scientia, 2023)
Beauty standards arise because of the construction of society. There is a myth that says that if a woman is beautiful and conforms to those standards of beauty, then she gets a lot of privileges. Digital media is one of the factors that makes this social construction happen. The researcher uses a qualitative research method with semiotic analysis techniques by Roland Barthes to help find the signs contained in the film Insatiable and interpret these signs according to the meaning of denotation, connotation,and myth. The theory used to support this research is Roland Barthes' theory of semiotics and the theory of social realityconstruction put forward by Peter L. Berger and Thomas Luckman. The film Insatiable represents beautiful women who conform to society's standards. Beautiful women also dress neatly and use makeup, more trusted by society, whatever they say will be justified, and they can play on someone's feelings.